Uji Aktivitas Antioksidan Ekstrak Etanol Karang Lunak Lobophytum sp. yang diperoleh dari Pantai Tongkaina, Kota Manado - Sumare, Chika Wanda; Yudistira, Adithya; Hariyanto, Yuanita Amalia (UNIVERSITAS SAM RATULANGI, 2026)
Soft coral contain bioactive compounds, such as alkaloids, alkaloids, flavonoids, and saponins, which have important antioxidant activity. This research aims to tested the antioxidant activity of ethanol extract of Lobophytum sp. using method DPPH (2,2-diphenyl-1-picrylhydrazyl). Phytochemical screening results show the presence of tannins, flavonoids, and saponins in the extract of Lobophytum sp. obtained from Tongkaina Beach, Manado City. Antioxidant activity test shows that the extract has high activity an IC50 value of 49,13 ppm which is categorized as very strong. Average value of percent inhibition increased along with increasing extract concetration, reaching 67,13% at concetration of 100 ppm. These findings indicate that Lobophytum sp. potential be a source of natural antioxidants that can be developed for prevention degenerative disease caused by free radicals. Further research necessary to explore more specific active compounds. Keywords: Antioxidant, IC50, Lobophytum sp., Percent inhibition, Phytochemical Screening